Origin of the water inflow at the Grib diamond mine (Arhangelsk region) (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: At the kimberlite deposit named after V. Grib, a surface mining method is used, which means that all water-bearing rocks above the mining floor have to be dewatered. The water is drained into dead pits along the entire perimeter of the quarry, which makes the mining process difficult and can lead to undesirable engineering-geological phenomena in the quarry (water breakthroughs, landslides, etc.). The purpose of our research was to study the processes of groundwater filtration during the drainage of the Grib mine, using numerical modelling. Methodology: The kimberlite pipe goes through Precambrian sedimentary rocks and is overlain by a stratum of Middle Carboniferous and Quaternary sediments. There are numerous rivers and lakes, as well as a tailing dump in the studied area. In order to determine the sources of water inflows into the quarry, we developed a numerical geofiltration model. The model takes into account all the elements of the drainage system, the interconnection of groundwater and surface waters, and the geological and hydrogeological features of the field. The theoretical model consists of four layers: Quaternary and Olmug-Okunev, Urzug-Voyerechensky, Padun, and Mezen systems. The water filtration problem was solved using the GMS MODFLOW package. Results and discussion: The process of identifying the model determined the character of the hydraulic connection between the water-bearing rocks and river and lake valleys, the positions of sources and sinks within the aquifers, as well as the filtration losses of the tailing dump of the Verkhotinsky GOK. It also identified the sources of water inflows to the drainage system of the quarry. The study determined that water inflows into the quarry are formed due to groundwater and atmospheric precipitation in the areas of close hydraulic connection between groundwater and surface water. Conclusions: The numerical model helped us to determine that the water inflows into the quarry originate from aquifers recharged by the infiltration from surface water objects and streams. We also determined the connection between the studied aquifer and the valleys of rivers and lakes, and identified the sources and sinks within the studied aquifer. Water losses from the tailing dump of Verkhotinsky GOK were estimated.
Keywords: groundwater; atmospheric precipitation; hydraulic connection between groundwater and surface water; filtration losses; water inflow into the quarry